Cross-sectional observational study of epidemiology of COVID-19 and clinical outcomes of hospitalised patients in North West London during March and April 2020. Issue 2 (18th February 2021) - Gopal Rao, Guduru; Allen, Alexander; Papineni, Padmasayee; Wang, Liyang; Anderson, Charlotte; McGregor, Alastair; Whittington, Ashley; John, Laurence; Harris, Miriam; Hiles, Stephen; Nicholas, Thomas; Adams, Katherine; et al.
Abstract : Objective: The aim of this paper is to describe evolution, epidemiology and clinical outcomes of COVID-19 in subjects tested at or admitted to hospitals in North West London. Design: Observational cohort study. Setting: London North West Healthcare NHS Trust (LNWH). Participants: Patients tested and/or admitted for COVID-19 at LNWH during March and April 2020 Main outcome measures: Descriptive and analytical epidemiology of demographic and clinical outcomes (intensive care unit (ICU) admission, mechanical ventilation and mortality) of those who tested positive for COVID-19. Results: The outbreak began in the first week of March 2020 and reached a peak by the end of March and first week of April. In the study period, 6183 tests were performed in on 4981 people. Of the 2086 laboratory confirmed COVID-19 cases, 1901 were admitted to hospital. Older age group, men and those of black or Asian minority ethnic (BAME) group were predominantly affected (p<0.05). These groups also had more severe infection resulting in ICU admission and need for mechanical ventilation (p<0.05). However, in a multivariate analysis, only increasing age was independently associated with increased risk of death (p<0.05). Mortality rate was 26.9% in hospitalised patients. Conclusion: The findings confirm that men, BAME and older population were most commonly and severely affected groups. Only older age was independently associated with mortality.